Analisis social return on investment program CSV berbasis ekonomi sirkular untuk pemberdayaan UMKM - Wibowo, Catur Prasetya; Ekowati, Dian (Nur Science Institute, 2025)
Creating Shared Value (CSV) offers a transformative approach to aligning business performance with societal progress. This study examines a CSV initiative by Universitas Airlangga that integrates circular economy principles to empower Micro, Small, and Medium Enterprises (MSMEs) in maggot and oyster mushroom cultivation in Surabaya, Indonesia. Conducted from February to May 2025, the program combined waste-to-resource innovation with community capacity building, directly targeting Sustainable Development Goals (SDGs) on poverty reduction, responsible production, and partnerships. Employing a mixed-method case study and the Social Return on Investment (SROI) framework, data were obtained through interviews, field observations, and financial analysis. The program achieved an exceptional SROI ratio of 32.02:1, indicating over thirty-two times the investment’s value returned as social benefits. Key outcomes include income growth, improved waste management, skill enhancement, and stronger community cohesion. This research advances the empirical understanding of CSV–circular economy integration and underscores the pivotal role of higher education institutions in catalyzing local-level social innovation.